The Kirov murder and Soviet history - Lenoe, Matthew E. (Matthew Edward) (Yale University Press, 2010)
Drawing on hundreds of newly available, top-secret KGB and party Central Committee documents, historian Matthew E. Lenoe reexamines the 1934 assassination of Leningrad party chief Sergei Kirov. Joseph Stalin used the killing as the pretext to unleash the Great Terror that decimated the Communist elite in 1937-1938; these previously unavailable documents raise new questions about whether Stalin himself ordered the murder, a subject of speculation since 1938. The book includes translations of 125 documents from the various investigations of the Kirov murder, allowing readers to reach their own conclusions about Stalin's involvement in the assassination.
Keywords: Kirov, Sergeĭ Mironovich, -- 1886-1934 -- Assassination.; Stalin, Joseph, -- 1878-1953.; Kommunisticheskai͡a partii͡a Sovetskogo Soi͡uza -- Purges.; Kirov, Sergeĭ Mironovich, -- 1886-1934; Stalin, Joseph, -- 1878-1953; Kommunisticheskai͡a partii͡a Sovetskogo Soi͡uza; Kommunističeskaja partija Sovetskogo Sojuza -- utrensningar.; Political purges -- Soviet Union -- History.; Political atrocities -- Soviet Union -- History.; Soviet Union -- History -- 1925-1953.; Purges politiques -- URSS -- Histoire.; Atrocités politiques -- URSS -- Histoire.; URSS -- Histoire -- 1925-1953.; Assassination; Political atrocities; Political purges; Soviet Union; Sovjetunionen -- historia -- 1900-talet.; 1925-1953; History